PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA E-BOOK TERHADAP PENGETAHUAN ASI EKSKLUSIF PADA IBU NIFAS DI PMB W TAHUN 2022 - Azis, Aninditya (Journal of Midwifery Tiara Bunda, 2024)
Background: Perineal tear is a wound that often occurs during childbirth. Perineal tears occur in almost all first deliveries and are not uncommon in subsequent deliveries. Perineal tears cause discomfort during the puerperium and even one of the causes of respiratory infection. Efforts to prevent perineal tears have been carried out, including perineal massage. Objective : To determine the relationship between perineal massage and perineal tears in multigravida birth mothers Methods : The type of research used is a one group design posttest only approach. This study used multigravida term pregnant women (37 weeks to 40 weeks pregnant) with the interpretation of delivery during July - August 2022, which in previous deliveries and had a history of perineal tears in previous deliveries. Meanwhile, to find out the perineal tear after the mother gives birth or when the mother gives birth by looking at the partograph monitoring tool. Results : Based on the results of the t-test analysis on the data of perineal massage on perineal tears in maternity mothers, the p value (0.000) < from 0.05, these results indicate that there is a relationship between perineal massage and perineal tears in multigravida maternity women. Conclusion : There is a relationship between perineal massage and perineal tears in multigravida birth mothers. Suggestion: It is hoped that it can be implemented in a midwife's practice because the perineal massage technique has been tested by data analysis to minimize perineal tears in pregnant women